MODERN APPROACHES TO THE EVALUATION OF FETAL HEART RATE - Галина Александровна Ушакова; Любовь Никитична Петрич (The Publishing House Medicine and Enlightenment, 2017)
Presented in the historical aspect of analytical review methods for studying fetal heart rate to assess his condition. The most widely used in recent years is the method of cardiotocography. However, when using this method have problems: subjectivity decryption cardiotocographic curves for visual evaluation, the complexity and the complexity of the mathematical methods of processing, the high frequency of false-positive and false-negative results. Modern computer programs are also not solve all the problems: the continuous monitoring of the increased frequency of caesarean section, but did not improve perinatal outcomes. The authors suggest that the lack of informative study of heart rate as an indicator of the state of the fetus due to the fact that the evaluation is carried out without taking into account the state of the whole system of mother - placenta - fetus. Presented in the historical aspect of analytical review methods for studying fetal heart rate to assess his condition. The most widely used in recent years is the method of cardiotocography. However, when using this method have problems: subjectivity decryption cardiotocographic curves for visual evaluation, the complexity and the complexity of the mathematical methods of processing, the high frequency of false-positive and false-negative results. Modern computer programs are also not solve all the problems: the continuous monitoring of the increased frequency of caesarean section, but did not improve perinatal outcomes. The authors suggest that the lack of informative study of heart rate as an indicator of the state of the fetus due to the fact that the evaluation is carried out without taking into account the state of the whole system of mother - placenta - fetus.